Water Sharing Geopolitics between India and Bangladesh: Recent Trends - Md. Mizanur Rahman (International Journal of Applied and Advanced Multidisciplinary Research, 2024)
The partnership between India and Bangladesh according to water sharing is complex by traditional, geographical, political, sociological, and economical issues. Understanding the present dynamics in water-sharing geopolitics is necessary for understanding the pathways of their bilateral partnership and the conjugation for regional sustainability and improvement. Both countries share almost 54 rivers for example Teesta, Ganges, Brahmaputra, and Meghna. These rivers are lifelines for Bangladesh and India, providing essential irrigation water, communication, and indigenous consumption. However, the unequal distribution of water and the influence of climate change have increased challenges over water management procedures. While both countries have contracted diverse treaties and agreements to manage shared rivers, implementation hazards and occasional breaches of trust have channeled their partners. Subsequently, the increasing demand for water due to population enrichment and industrialization shapes modern challenges for stable water mechanisms. This research aims to describe the present dynamics in water-sharing geopolitics between India and Bangladesh, examining the evolving trends, key factors, and their conjugations for regional sustainability and collaboration. By extending the complexities of this critical view of their partnership, this study seeks to contribute to a deeper realization of South Asia's geopolitical arena and prosecutorial dynamics for cooperative water distribution strategies.